Telaah Kritis Terhadap Upaya Peningkatan Literasi Keuangan Melalui Tabungan Sekolah - Muhammad Rifqi Hidayat; Rusdiana Rusdiana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
The purpose of this study is to analyze how the implementation of efforts to increase financial literacy through student savings at elementary school level students in the city of Banjarmasin, as well as to formulate an ideal student savings concept to maximize the results of efforts to increase financial literacy. This research is qualitative field research accompanied by a quantitative survey to 412 respondens from 18 different schools of students' saving behavior, which then will be analyzed descriptively. The results showed that only 38.1% of respondents independently allocated a portion of their allowance for savings. 11 of the 18 schools that become research sites manage their student savings independently with manual recording via a passbook or Microsoft Excel. Seven other schools have collaborated with banking institutions, but banks are only able to visit one to two times per week. Thus, parents of students need to have a good understanding of how to teach their children to save. The recording of student savings should also be supported by a web-based system that can be monitored by the teacher, students, and student guardians. Schools should also continue to receive student savings deposits every day with independent registration, to then be deposited at the same time when the bank visits the school.